2006
DOI: 10.1113/jphysiol.2006.111559
|View full text |Cite
|
Sign up to set email alerts
|

Autophosphorylation of αCaMKII is not a general requirement for NMDA receptor‐dependent LTP in the adult mouse

Abstract: Autophosphorylation of α‐Ca2+/calmodulin kinase II (αCaMKII) at Thr286 is thought to be a general effector mechanism for sustaining transcription‐independent long‐term potentiation (LTP) at pathways where LTP is NMDA receptor‐dependent. We have compared LTP at two such hippocampal pathways in mutant mice with a disabling point mutation at the Thr286 autophosphorylation site. We find that autophosphorylation of αCaMKII is essential for induction of LTP at Schaffer commissural–CA1 synapses in vivo, but is not re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 48 publications
(65 reference statements)
5
73
0
Order By: Relevance
“…The T286A mutants can form contextual LTM although they have fully blocked NMDA receptor-dependent synaptic strengthening in hippocampal area CA1, as indicated by previous electrophysiological experiments (10)(11)(12)(13)(14). We confirmed that late CA1 LTP is blocked after strong electrical stimulation, and we show that training-induced synaptic strengthening is deficient in hippocampal area CA1, in the amygdala, neocortex, and striatum, and in the T286A mutants, using imaging of the expression of three IEGs (Zif268, c-Fos, and Nur77) that are critical transcription factors for long-lasting synaptic strengthening (17,18).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The T286A mutants can form contextual LTM although they have fully blocked NMDA receptor-dependent synaptic strengthening in hippocampal area CA1, as indicated by previous electrophysiological experiments (10)(11)(12)(13)(14). We confirmed that late CA1 LTP is blocked after strong electrical stimulation, and we show that training-induced synaptic strengthening is deficient in hippocampal area CA1, in the amygdala, neocortex, and striatum, and in the T286A mutants, using imaging of the expression of three IEGs (Zif268, c-Fos, and Nur77) that are critical transcription factors for long-lasting synaptic strengthening (17,18).…”
Section: Discussionmentioning
confidence: 96%
“…T286A mutants have substantial deficits in synaptic strengthening induced by electrical stimulation (10)(11)(12)(13)(14). The expression of the IEGs Zif268 and c-Fos has been shown to be a prerequisite for late LTP (17,18).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A broad range of genetic lesions of ␣CaMKII signaling has been demonstrated to block both learning and LTP (Elgersma et al 2004). In particular, autophosphorylation of ␣CaMKII at threonine-286 in response to Ca 2+ influx, which switches the kinase into a Ca 2+ /calmodulin-independent or autonomously active state, provides a crucial step (Miller and Kennedy 1986;Fukunaga et al 1995;Tan and Liang 1996;Ouyang et al 1997;Rodrigues et al 2004), since knock-in mice with a targeted point mutation (T286A) that prevents autophosphorylation at this site exhibit deficits in hippocampal LTP and memory formation (Giese et al 1998;Ohno et al 2002Ohno et al , 2005Ohno et al , 2006Need and Giese 2003;Irvine et al 2005;Cooke et al 2006). Although the mechanisms by which ␣CaMKII autophosphorylation contributes to learning have been well documented, its role in memory extinction remains to be determined.…”
mentioning
confidence: 99%